BIOFUEL: ALTERNATIVE FOR APPLICATIONS IN OXI-COMBUSTION THERMAL PROCESSES - Lucian Paunescu; Gheorghe Surugiu; Eniko Volceanov (Nonconventional Technologies Review)
Bioenergy, as a form of regenerable power, is an excellent alternative to ensure a clean and healthy environment and at the same time, to preserve natural energy resources that are constantly decreasing. Due to their biological origin, biofuels used in combustion processes contribute to the releasing of non-polluting gases in ambience with low percentages of CO2, CO, NOx, etc. The paper presents the project of an oxy-biological fuel burner using glycerin and ethanol as biofuels, suitable for industrial thermal processes at high temperature. The project was based on the own outcomes previously obtained in 2022, adding new contributions to improve the combustion process. Keeping the heat power of the burner at 60 kW, the glycerin and ethanol flows were adopted at 10 and 1.11 kg·h-1, i.e. a mass ratio of 9.0 than 8.1 used in the previous experiment. Residual gas composition measured under these conditions showed under 0.05 vol. % CO2, 0 vol. % CO as well as below 183 mg·m3 N-1 NO and under 200 mg·m3N-1 NO2.